1992
DOI: 10.1017/s0143385700007057
|View full text |Cite
|
Sign up to set email alerts
|

Finite beta-expansions

Abstract: We characterize numbers having finite β-expansions where β belongs to a certain class of Pisot numbers: when the β-expansion of 1 is equal to a1a2…am, where a1≥a2≥…≥am≥1 and when the β-expansion of 1 is equal to t1t2…tm(tm+1)ω where t1≥t2≥…≥tm>tm+1≥1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
141
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(145 citation statements)
references
References 12 publications
3
141
0
1
Order By: Relevance
“…closed unit disc |z| 1 with at least one conjugate lying on the circle |z| = 1). Finite β-expansions have been studied in [9] and [11]; those results are also related to Pisot numbers.…”
Section: Introductionmentioning
confidence: 99%
“…closed unit disc |z| 1 with at least one conjugate lying on the circle |z| = 1). Finite β-expansions have been studied in [9] and [11]; those results are also related to Pisot numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Frougny and Solomyak [18] have studied situations in which one can guarantee that a given Pisot number is a simple beta-number.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exist Pisot numbers that do not fullfill (F), such as all numbers with non purely periodic quasi-greedy β-expansion of 1. In [7], it is also shown that if…”
Section: Introductionmentioning
confidence: 99%
“…In [10], and before in [8], the authors posed the question whether Hypothesis B, introduced in [8], and the finiteness property (F), introduced in [7], are equivalent. Hypothesis B is a condition on the carries of the digits in the expansion of positive integers in a base system defined by a linear recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation